2011
DOI: 10.1002/macp.201100012
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Vesicle‐Forming Block Copolymers in Aqueous Solutions

Abstract: The binary phase diagram of amphiphilic poly(ethylene oxide)‐block‐poly(γ‐methyl‐ε‐caprolactone) block copolymers in water is examined for four polymers having the same hydrophilic block length but different hydrophobic block lengths across the whole concentration range. The bulk polymers show no ordered morphology. With increasing water concentration the polymers undergo transitions from lamellar phases to packed vesicles and subsequently all polymers self‐assemble into vesicles in dilute aqueous solutions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 49 publications
0
34
1
Order By: Relevance
“…17,18,8385 However, as far as we are aware, the present study is the first example of such structures being formed during a PISA synthesis. These results suggest that PISA formulations offer considerable potential for the convenient and efficient generation of block copolymer-based nanostructured fluids.…”
Section: Saxs Analysismentioning
confidence: 74%
“…17,18,8385 However, as far as we are aware, the present study is the first example of such structures being formed during a PISA synthesis. These results suggest that PISA formulations offer considerable potential for the convenient and efficient generation of block copolymer-based nanostructured fluids.…”
Section: Saxs Analysismentioning
confidence: 74%
“…Lipid membranes are omnipresent in nature and serve as a role model in the design of synthetic analogues with improved stability and functionality. [30] To create polymersomes/membranes in our laboratories, we used amphiphilic block-copolymers, including (PMOXA-b-PDMS-b-PMOXA), [31] (PEG-b-PMCL), [32] (PEG-b-PMCL-b-PDMAEMA) [33] and (PB-b-PEG). [34] Initially we struggled to extend the applicable self-assembling materials to include amphiphilic peptides.…”
Section: Amphiphilic Peptides Based On a Repetitive W-l Sequencementioning
confidence: 99%
“…Braun et al have studied low molecular weight poly(ethylene oxide) 23 -bpoly(γ-methyl-ε-caprolactone) y = 2 5 , 3 2 , 4 4 , 5 4 (PEO 2 3 -b-PMCL y=25,32,44,54 ) over the entire polymer concentration range in aqueous solutions. 22 These studies showed that the most prevalent self-assembled nanostructures for all of the diblock copolymer compositions are lamellar bilayers and vesicles. However, PEO 23 -b-PMCL 25 also forms hexagonally packed cylinders at low polymer concentrations, and PEO 23 -b-PMCL 54 forms inverse hexagonally packed cylinders at high polymer concentrations.…”
Section: ■ Introductionmentioning
confidence: 99%